Learning Citizen's Voice Through Twitter, A Sign Of E-Engagement In Bandung City - HANAN KHAIRANY, SHAFIRA
The current development of technology, information and communications (ICT) has spawned an innovation trend in improving public services at city level, where cities have used technology as a method to improve municipal services by increasing public involvement and collaboration in urban development. One of the urban concept that utilizes ICT is smart city or smart city. The existence of information and communication technology (ICT) and the increasing use of internet has changed the process of online communication in the public sphere. This phenomenon has also changed the way people receive and disseminate information and communicate using digital communication. This poses a challenge for the government to facilitate the shifting of community communication patterns that change from traditional communication lines to internet and wireless communication-based interaction channels through the utilization of ICT. Basically, the main thing in smart city development is the city's service to the community. Various cities including Bandung City have used technology as one method to improve service delivery by increasing public involvement and collaboration. To achieve greater public engagement and improve public services, the city must add new methods, including digital and mobile technologies. All SKPD Bandung at this time has had a Twitter account as a form in facilitating the shift of communication patterns of the community that changed from traditional communication lines to internet and wireless communication-based interaction channels through the utilization of ICT since 2013. But in fact, not all SKPD utilizing social media optimally. This causes the necessary analysis to identify the extent of utilization of social media Twitter by SKPD Bandung to encourage community involvement in realizing the city of Bandung as a Smart City. The purpose is done by identifying the content type and level of community involvement (e-Engagement) in social media Twitter SKPD Bandung. This is a qualitative research with the method of content analysis and descriptive statistic method to know the general description of social media Twitter. Broadly speaking, social media Twitter SKPD is classified as active and has a commitment in using Twitter namely Dishub, DPU, Distaru, Satpol PP, and Dinsos, which is seen from the average tweet that tend to regularly provide information or tweet on a regular basis. In general, DPU, Distaru, Dinsos, Dishub and Satpol PP use Twitter to disseminate information (78%) than to interact to the community (22%). The most dominant type of information is activities and work programs related to SKPD of 54%. In essence, Twitter social media allows to establish communication and collaborate in 2 and many directions. And the use of social media Twitter SKPD is currently used for inform and consult.